ONLINE PURCHASE OPTIMIZATION STRATEGY VIA INSTAGRAM SOCIAL MEDIA FOR STUDENTS IN SURABAYA - Erwan Aristyanto; Agus Sarwo Edi (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
E-commerce is the purchase, sale and marketing of goods or services through an electronic or internet system. For that the research aims to find out the influence of Price, Product Quality and Celebrity Endorser toward Online purchasing decision through social media Instagram. In this research taking samples intentionally using a quota sampling of 100 respondents from Surabaya college students. The sampling technique uses nonprobability sampling and the sampling method uses accidental sampling. The analytical method used is multiple linear regression analysis. And the results of the research show that simultaneously there is a significant influence between the variable price, product quality and celebrity endorser on purchasing decisions. To partially, the price has a not significant and negative value effect on purchasing decisions, while for product quality and celebrity endorser has a significant effect on purchasing decisions.